« Little Wise Men : Three Friends and the Public Administration World They Made » - Pierre-Yves Saunier (Transatlantica)
This article examines the transnational endeavors that presided over the establishment and maintenance of a structured regime of circulation in public administration considered as a profession, a theory, a discipline and a governmental practice. The three individuals who are at the core of the article were vital in organizing this regime, and their contribution to integrate the contribution of inter-governmental organizations, non governmental organizations, professional US societies and US universities has left a deep imprint in the field. Assessing their contribution is the opportunity to develop some hunches and hypothesis on the existence of “universalizing projects” that have shaped the interconnection and interdependency of our modern world.